Sarcoidosis-related small fiber neuropathy: Focus on fatigue, pain, restless legs syndrome, and cognitive function - Raasing, Lisette; Veltkamp, Marcel; Datema, Mirjam; Korenromp, Ingrid; Grutters, Jan C.; Vogels, Oscar J.M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background: Of all sarcoidosis patients 60-90% suffer from fatigue, 40-80% experience small fiber neuropathy, 35% suffer from cognitive impairment and 16-52% experience restless legs syndrome (RLS). The prevalence, severity and association between fatigue, pain, RLS and cognitive impairment in patients with sarcoidosis and small fiber neuropathy (SFN) is unknown and will be investigated in this study.Methods: Healthy controls, patients with sarcoidosis with SFN and patients with sarcoidosis without SFN were compared. They completed multiple questionnaires (fatigue assessment scale (FAS), RLS rating scale, visual analogue scale (VAS) score for pain and cognitive failure questionnaire (CFQ)), to estimate the prevalence, severity, and correlation of fatigue, RLS, pain, SFN and cognitive impairment.Results: Twenty healthy volunteers, 49 patients with sarcoidosis without SFN and 48 patients with sarcoidosis with SFN were included. Fatigue was the most prevalent symptom in patients with sarcoidosis with SFN (97%), followed by pain (85%), RLS (67%) and cognitive impairment (46%). Moreover, the severity of fatigue, pain, RLS and cognitive impairment was higher in patients with sarcoidosis with SFN compared with patients with sarcoidosis without SFN (resp. p=0.0006, p=0.003, p=0.02 and p=0.009). Finally, the FAS, RLS, VASmean, VASmax and CFQ showed a strong correlation with each other (R> 0.5, p